RANCANG BANGUN ALAT PEMARUT KELAPA TIPE SCREW (Design of Screw Type Coconut Guider) - Domen Sitohang; Achwil Putra Munir; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT In improving agricultural production, including pre-to post-harvest facilities and infrastructure, require, effective as agricultural tools and machines. This research was aimed to design and test screw type coconut grater type using coconut and new material. The parameters observed were the effective capacity of the tool, ungrated percentage of copra, percentage of remaining copra and economic analysis. The results should that the effective capacity was 60.606 kg/hour, the percentage of ungrated material was 1,3 %, the percentage of copra were left at 1,7 % and the value of economic analysis for the cost of goods in the first year was Rp 191.060 and the fifth year was Rp 193.458, break even point (BEP) was 69,.744 kg in the first year and 871,458 kg in the fifth year, and the value of Net present value (NPV) was 7,5 %, and the value of internal rate of return (IRR) was 25,4 %. Keywords: Coconut Grater Screw Type, Copra ABSTRAK Dalam meningkatkan produksi pertanian yang meliputi prapanen sampai pascapanen memerlukan sarana dan prasarana yang efektif seperti alat dan mesin pertanian. Penelitian ini bertujuan untuk merancang dan menguji alat pemarut kelapa tipe screw dengan menggunakan kelapa sebagai bahan bakunya. Parameter yang diamati yaitu kapasitas efektif alat, presentase kopra tidak terparut, presentase kopra yang tertinggal dan analisis ekonomi. Dari hasil penelitian diperoleh kapasitas efektif alat sebesar 60,606 kg/jam, presentasse bahan tidak terparut sebesar 1,3 %, presentase kopra yang tertinggal sebesar 1,7 % dan nilai analisis ekonomi untuk biaya pokok pada tahun pertama sebesar Rp 191,060 dan pada tahun kelima sebesar Rp 193,458, break even point (BEP) 699,744 kg pada tahun pertama dan 871,458 kg pada tahun kelima, dan nilai Net present value (NPV) sebesar 7,5 %, nilai Internal rate of return (IRR) sebesar 25,4 %.   Kata Kunci : Alat Pemarut Kelapa Tipe Screw, Kelapa Kopra